2014
DOI: 10.15406/jnhfe.2014.01.00029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lactic Acid Bacteria and Enterobacteriaceae Counts in Bulgarian Probiotic Products by TEMPO® System and ISO Methods

Abstract: Submit Manuscript | http://medcraveonline.com pathogenic bacteria. Therefore, rigorous hygienic precautions and adequate monitoring of the process environment and the finished product should be in place in order to ensure the quality and safety of the final product.The common microbiological parameters monitored for quality and safety of dairy products are applicable to probiotic products as well. Of these, Enterobacteriaceae is usually tested as a hygiene indicator intended to verify the hygiene programs appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The TEMPO system is an automated most probable number (MPN), which is based on the measurements of fluorescence method for enumerating aerobic bacteria and specific pathogens in foods [48][49][50]. Further, our results are in accordance with those observed by Katase and Tsumura [51], Blagoeva et al [52], and Łobacz et al [53], who compared the results of the TEMPO system with the corresponding methods to enumerate total aerobic bacteria, coliforms, Enterobacteriaceae, yeast and mold, S. aureus, and lactic acid bacteria. Moreover, comparisons of different methods for quantifying L. monocytogenes biofilms have shown that among the indirect counting methodologies, the one that gives the best results is the TEMPO system [54].…”
Section: Bacterial Enumeration On Polymer Surfacessupporting
confidence: 91%
“…The TEMPO system is an automated most probable number (MPN), which is based on the measurements of fluorescence method for enumerating aerobic bacteria and specific pathogens in foods [48][49][50]. Further, our results are in accordance with those observed by Katase and Tsumura [51], Blagoeva et al [52], and Łobacz et al [53], who compared the results of the TEMPO system with the corresponding methods to enumerate total aerobic bacteria, coliforms, Enterobacteriaceae, yeast and mold, S. aureus, and lactic acid bacteria. Moreover, comparisons of different methods for quantifying L. monocytogenes biofilms have shown that among the indirect counting methodologies, the one that gives the best results is the TEMPO system [54].…”
Section: Bacterial Enumeration On Polymer Surfacessupporting
confidence: 91%
“…The most probable number method is based on that a liquid medium turns turbid during bacterial growth (Bibiloni et al, 2001;Sutton, 2010;Angelov, 2014). By making a 10-fold serial dilution of a bacterial cell solution in replicates, the point will be reached where the solution is so diluted that only a few of the replicates of a certain dilution give rise to turbidity.…”
Section: Most Probable Numbermentioning
confidence: 99%
“…The number of tubes with confirmed turbidity, thus growth, at the different dilutions can be used to estimate the number of viable cells in the original sample by utilizing premade tables based on statistics using 95% confidence intervals. Although not traditionally used for viability measurements in probiotics, there are a few examples (Bibiloni et al, 2001;Angelov, 2014).…”
Section: Most Probable Numbermentioning
confidence: 99%